Neonatal Dengue: A Case Series of Three Patients with a Wide Clinical Spectrum - Anggita Dian Karera; Hana Amelia; Delta Iswara; Din Alfina (CV. AFDIFAL MAJU BERKAH, 2025)
Neonatal dengue is an uncommon but clinically important condition that can present with a wide range of symptoms. This report describes three neonatal dengue cases with distinct clinical manifestations and emphasizes the importance of early recognition. The objective of this case series is to outline the clinical features, laboratory findings, and treatment outcomes of the affected neonates. All three patients presented with fever accompanied by various symptoms, including seizures, jaundice, respiratory distress, and significant thrombocytopenia. Diagnostic evaluation consisted of serological testing, hematological assessment, and imaging studies when needed. The lowest platelet counts ranged from 10,000 to 14,000 per microliter, although none of the neonates experienced major bleeding or shock. All patients received supportive treatment, including fluid management, monitoring, and therapy tailored to presenting symptoms. Each neonate demonstrated gradual improvement and was discharged in stable condition following appropriate observation. These cases highlight that neonatal dengue may resemble sepsis and thus requires a high level of diagnostic vigilance, particularly in endemic areas or when maternal dengue is suspected. Early serological testing in both mother and infant is valuable for timely diagnosis. Supportive care and close monitoring contribute significantly to preventing complications and achieving favorable outcomes.